2019
DOI: 10.1039/c8cc08124g
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and stable air-processed hole-transport-material free carbon based perovskite solar cells with caesium incorporation

Abstract: Cs containing triple cation HTM-free carbon based PSCs were fabricated out of a glovebox showing the best performance over 15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Although the CCE‐based HTL‐free PSC presents the most significant merits of low cost and simple fabrication procedure, the PCE value is still lower than that of the metal‐CE‐based PSC. In addition to investigating novel carbon materials and interface engineering techniques to optimize the interfacial contact and the energy level alignment, developing more stable inorganic perovskites, and exploring low‐temperature in‐air assembly techniques for the CCE‐based PSC are also significant for application‐oriented mass production ip = 2.69×105ACn1.5D0.5v0.5 where A is the electrode area, C is the concentration of redox species, n is the number of electrodes involved in the redox reaction, D is the diffusion coefficient, and v is the scan rate.…”
Section: Carbon Counter Electrodes In the Perovskite Solar Cell (Psc)mentioning
confidence: 99%
“…Although the CCE‐based HTL‐free PSC presents the most significant merits of low cost and simple fabrication procedure, the PCE value is still lower than that of the metal‐CE‐based PSC. In addition to investigating novel carbon materials and interface engineering techniques to optimize the interfacial contact and the energy level alignment, developing more stable inorganic perovskites, and exploring low‐temperature in‐air assembly techniques for the CCE‐based PSC are also significant for application‐oriented mass production ip = 2.69×105ACn1.5D0.5v0.5 where A is the electrode area, C is the concentration of redox species, n is the number of electrodes involved in the redox reaction, D is the diffusion coefficient, and v is the scan rate.…”
Section: Carbon Counter Electrodes In the Perovskite Solar Cell (Psc)mentioning
confidence: 99%
“…Among the four kinds of CPSCs, planar and quasi‐planar CPSCs adopt architectures quite similar to metal PSCs; thus, bulk engineering of PVSK done in metal PSCs could be borrowed . However, it is different for the other two structures.…”
Section: Progress In Power Conversion Efficiencies Of the Cpscs (Htm‐mentioning
confidence: 99%
“…Thus, hole‐transporting‐material (HTM, or hole‐transport‐layer/HTL), on which metal‐electrodes‐based PSCs (noted by metal PSCs) are usually relied, is not necessarily used in CPSCs, leading to HTM‐free devices . From the pioneered works done by Han, Yang, Zhao, and coworkers, CPSCs have attracted ever‐increasing attention . As long as the formation process of PVSK is considered, four kinds of architectures have been adopted: meso CPSCs, embedment CPSCs, planar CPSCs, and quasi‐planar CPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The unsatisfactory efficiency of HCF-PSCs is mainly ascribed to low hole transport efficiency, high charge recombination, undesired energy band diagram match and imperfect contacts at the interface of the perovskite/carbon electrode as well as poor carbon adhesion and insufficient incident light by carbon electrodes. 9,10 In order to further improve the efficiency of HCF-PSCs, many efforts have been made for developing advanced and stable perovskite composites with organic or inorganic materials [11][12][13][14][15][16][17][18][19][20][21] and designing novel device congurations with the interfacial engineering strategy. 10,[22][23][24][25][26] The perovskite-based composition engineering with a mixedcation/halide have signicantly enhanced optical and electronic properties, electron-hole extraction and transport as well as intrinsic hybrid-perovskite structure stability.…”
Section: Introductionmentioning
confidence: 99%
“…10,[22][23][24][25][26] The perovskite-based composition engineering with a mixedcation/halide have signicantly enhanced optical and electronic properties, electron-hole extraction and transport as well as intrinsic hybrid-perovskite structure stability. [12][13][14][15][27][28][29] Han et al pioneered HCF-PSCs based on mixed-cation or mixed-halide perovskites ((5-AVA) x MA 1Àx PbI 3Ày (BF 4 ) y , 5-AVA: 5-aminovaleric acid) by controlling the ratio of two cations or halides, thus endowing the corresponding cells with an improved PCE over 12% and operational stability. 12,13 Interestingly, Grancini et al showed that ultra-stable 2-dimensional/3-dimensional (2D/3D) perovskite-based composites (i.e., (HOOC(CH 2 ) 4 NH 3 ) 2 PbI 4 / MAPbI 3 ) could be formed via 5-AVAI composition engineering.…”
Section: Introductionmentioning
confidence: 99%